Evaluating Golden‐winged Warbler use of alder and aspen communities managed with shearing in the western Great Lakes. Issue 3 (23rd March 2023) - Buckardt Thomas, Anna; McNeil, Darin J.; Larkin, Jeffery L.; Johnson, Kirsten E.; Roth, Amber M.
Abstract: Best management practices are often written by researchers to guide land managers and landowners in the creation of habitat for wildlife species of interest. These documents are based on research evaluating the habitat needs of a species, but they also describe tools and strategies managers can implement to create or restore desired conditions. Shrub and sapling shearing is a management practice often used to improve habitat for early‐successional species, yet little monitoring or research has focused on wildlife response to shearing. The goal of this research was to formally evaluate the effect of shrub and sapling shearing as a best management strategy for Golden‐winged Warbler ( Vermivora chrysoptera ) conservation at a regional scale. Specifically, we surveyed for male Golden‐winged Warblers during the breeding season in sheared sites and untreated reference sites across portions of the western Great Lakes to assess the effects of (1) management status (i.e., sheared aspen or alder vs. untreated sites) and (2) patch‐level vegetation characteristics on male abundance. We found that male Golden‐winged Warbler abundance was twice as high in sheared sites than in mature reference sites and peaked when sapling cover was ~40%. Male abundance was also negatively associated with percent cover of forbs and nonvegetated ground. These findings highlight the importance of patch‐level heterogeneity when implementing shearing treatments for Golden‐winged Warblers and demonstrate the potential need for pretreatment site assessments to help focus conservation efforts for this species. Ultimately, our results support the use of a site‐specific, nuanced approach to shearing implementation to maximize cost efficiency and desired species outcomes.